NILAI KOMPENSASI EKONOMI TERHADAP PENCEMARAN PERAIRAN DI PANTAI KOTA MAKASSAR - Hamzah Hamzah; Achmad Fahrudin; Heffni Efendi; Ismudi Muchsin (Jurnal Bisnis Perikanan (Journal of Fishery Business), 2015)
This research was intended to calculate values of tourism and fishery economic loss due to aquatic pollution by applying a dynamic model. Data collected is obtained through direct field and from data base Fisheries department, ecotourism and local government.Data process with Stella versi 9.0.2 High Performance System, Inc., 2007. Results of this research showed a simulation with budget allocation of sewage end processing installation (IPAL) and working effectivity of 30%, it was gained net benefit in fishery and tourism as much as Rp1.469.772/month and total benefit received up to the 10th year was Rp12.538.802.584.706.- Model simulation of compensation of insentive value was Rp1.153 person//month at the initial period to Rp8.397.567,- end of this simulation. If compared between the compensation value and the insentive value received by the community, there was a net surplus that give an economic advantage between values paid by the community to solve the pollution and benefit enjoyed by the community. At theoptimism scenario model, it was found impact of economic increase, whereas, results of the pessimism model gave a decrease by introducing sewage processing installation.